Efektivitas Penurunan Chemichal Oxygen Demand (COD) dan pH Limbah Cair Industri Tahu dengan Tumbuhan Melati Air melalui Sistem Sub-Surface Flow Wetland - Anggrika Riyanti; Monik Kasman; Muhammad Riwan (Jurnal Daur Lingkungan, 2019)
Some of tofu industries in Jambi City are household industries, where the wastewater from processing unit was disposed of into the environment without treatment. This study aims to analyze the effect of detention time and the effectiveness of decreasing COD concentration and pH neutralization on wastewater of  tofu industry using a sub surface flow - wetlands (SSF-wetland) system combined with a filtration system. The plant selected in this study was water jasmine (Echinodorus palaefolius).  Variables of waste water detention time in the reactor are 5, 7, 9, 11, 13 and 15 days.  Decreasing of COD concentration and increasing of pH were analyzed by comparing influent and effluent from wastewater samples, also the effect of detention time on the effectiveness of parameter reducing on each system.  The water quality standard  refers to the regulation of the Minister of Environment and Forestry Number 68 Year 2016.   The results showed excellent performance from a combination of the two systems where an initial pH with range of 3 increase to pH 6.5-7.  The efficiency of reducing COD concentration reached 47-94% during the 15-day detention time with concentration value 125 mg / l, close to the standard value 100 mg / l. The residence time has more significant effect on the reduction of COD in the SSF-Wetland system than the filtration system. Whereas in pH parameters, the residence time does not have a significant effect on both systems.